Manajemen Pengelolaan Dana Desa Tahun 2024 Untuk Pembangunan Infrastruktur di Desa Rantau Kermas Kecamatan Jangkat Kabupaten Merangin Provinsi Jambi - Melda Sari; Sutia Budi (Universitas Maritim AMNI Semarang, 2024)
Village fund management is a key element in accelerating development in rural areas. This article evaluates the management of village funds in 2024 in Rantau Kermas Village, Jangkat District, Merangin Regency, Jambi Province, with a focus on projects to improve farming roads and normalize river water for rice fields. The methodology used involves active community participation in project planning, implementation, monitoring and reporting, with technical assistance from students of the Ahmad Dahlan Institute of Technology and Business (ITB AD) Jakarta. The research results show that improving the 4 kilometer long agricultural road succeeded in increasing accessibility and reducing agricultural operational costs, while normalizing the 3 kilometer river succeeded in improving irrigation and reducing the risk of flooding, thereby increasing agricultural productivity. The principles of transparency and accountability are implemented through the formation of a Village Fund Management Team (TPDD) and regular reporting involving all elements of society. The discussion identified challenges such as limited capacity of village officials and resistance to change, which were successfully overcome through training and a participatory approach. The implications of this research show that effective village fund management can be a model for other villages in achieving sustainable and inclusive development.